Évolution de principaux indicateurs de la santé de la population francophone et anglophone de l’Ontario : 2001-2014. Résultats de l’enquête sur la santé dans les collectivités canadiennes - Bouchard, Louise; Batista, Ricardo; Reaume, Michael (Université d’Ottawa et Institut du savoir Montfort, 2021)

Étude sur les populations âgées et l’accès aux soins de longue durée en français en Ontario - Belanger, Christopher; Timony, Patrick; Glaude, Normand; Bouchard, Louise (Université d'Ottawa, 2024)
Ce rapport présente une analyse de la demande et de l’offre de services de santé en français (SSF) dans le secteur des soins de longue durée (SLD) en Ontario. En nous appuyant sur des données publiques ainsi que sur des données administratives fournies par le ministère de la Santé de l’Ontario, le rapport examine : 1. la demande régionale de SSF, évaluée selon la population ontarienne âgée de 65 ans et plus et la population francophone de ce groupe d’âge ; 2. l’offre de SSF, mesurée par le nombre et le type de foyers présents dans chaque région, ainsi que par les compétences linguistiques en français de leur personnel.

Study of aging populations and access to French-language long-term care in Ontario - Belanger, Christopher; Timony, Patrick; Glaude, Normand; Bouchard, Louise (Université d'Ottawa, 2024)

mobilisation collective pour une santé en français en ontario. closm santé - Forest, Mariève; Gilbert, A.; Bouchard, Louise (Le moment Monfort dans la francophonie canadienne, 2024)

Multimorbidity: Exploring determinants and differences between Francophones and Anglophones in Ontario - Duong, Patrick; Batista, Ricardo; Lizotte, Mathieu; Sauvé-Schenk, Katrine; Bouchard, Louise (2024)

La multimorbidité : prévalence et déterminants chez les francophones et les anglophones de l’Ontario [affiche] - Duong, Patrick; Lizotte, Mathieu; Batista, Ricardo; Sauvé-Schenk, Katrine; Bouchard, Louise (Colloque 103 – L’offre des services de santé dans les langues minoritaires, dans le cadre du 92e Congrès de l’Acfas, 2025)

Santé de la population francophone et anglophone âgée de 65 ans et plus de l’Ontario [affiche] - Bouchard, Louise; Batista, Ricardo; Duong, Patrick; Sauvé-Schenk, Katrine; Lizotte, Mathieu (Colloque 103 – L’offre des services de santé dans les langues minoritaires, 92e Congrès de l’Acfas, 2025)

Expériences en foyers de soins de longue durée et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de recherche - van Kemenade, Solange; Benoît, Josée; Bouchard, Louise; Sauvé-Schenk, Katrine; Savard, Jacinthe (Chaire de recherche de l’Université d’Ottawa et de l’Institut du savoir Montfort sur la santé des francophones de l’Ontario (2019-2024), Université d’Ottawa, 2025)
L’étude rapportée dans ce rapport visait à cerner la disponibilité de services en français dans les FSLD, leur accès, ainsi que l’impact de barrières linguistiques sur la santé et le bien-être, la qualité et la sécurité de soins à partir des perspectives des gestionnaires, des intervenant·es et des personnes résidant dans un FSLD ou de leur proche aidant·e. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des foyers, qu’ils soient à caractère francophone, désignés, identifiés ou non identifiés. Ce rapport intégral présente des résultats détaillés, accompagnés de plusieurs citations de participants.

Expériences en foyers de soins de longue durée et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de synthèse - van Kemenade, Solange; Benoît, Josée; Bouchard, Louise; Sauvé-Schenk, Katrine; Savard, Jacinthe (Chaire de recherche de l’Université d’Ottawa et de l’Institut du savoir Montfort sur la santé des francophones de l’Ontario (2019-2024), Université d’Ottawa, 2025)
L’étude rapportée dans ce rapport de synthèse visait à cerner la disponibilité de services en français dans les FSLD, leur accès, ainsi que l’impact de barrières linguistiques sur la santé et le bien-être, la qualité et la sécurité de soins à partir des perspectives des gestionnaires, des intervenant·es et des personnes résidant dans un FSLD ou de leur proche aidant·e. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des foyers, qu’ils soient à caractère francophone, désignés, identifiés ou non identifiés. Ce rapport de synthèse en décrit les principaux constats, accompagnés de quelques citations de participants.

Ascertaining the Francophone population in Ontario: validating the language variable in health data - Batista, Ricardo; Hsu, Amy T.; Bouchard, Louise; Reaume, Michael; Rhodes, Emily; Sucha, Ewa; Guerin, Eva; Prud'homme, Denis; Manuel, Douglas G.; Tanuseputro, Peter (BMC Medical Research Methodology, 2024)
Abstract Background Language barriers can impact health care and outcomes. Valid and reliable language data is central to studying health inequalities in linguistic minorities. In Canada, language variables are available in administrative health databases; however, the validity of these variables has not been studied. This study assessed concordance between language variables from administrative health databases and language variables from the Canadian Community Health Survey (CCHS) to identify Francophones in Ontario.

Quality and safety in long-term care in Ontario: The impact of language discordance - Batista, Ricardo; Prud'homme, Denis; Rhodes, Emily; Hsu, Amy; Talarico, Robert; Reaume, Michael; Guérin, Eva; Bouchard, Louise; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2021)
Objectives This study compared quality indicators across linguistic groups and sought to determine whether disparities are influenced by resident-facility language discordance in long-term care. Design Population-based retrospective cohort study using linked databases. Setting and Participants Retrospective cohort of newly admitted residents of long-term care facilities in Ontario, Canada, between 2010 and 2016 (N=47,727). Individual residents' information was obtained from the Resident Assessment Instrument Minimum Data Set (RAI-MDS) to determine resident's primary language, clinical characteristics, and health care indicators. Measures Main covariates of interest were primary language of the resident and predominant language of the long-term care facility, which was determined using the French designation status as defined in the French Language Services Act. Primary outcomes were a set of quality and safety indicators related to long-term care: worsening of depression, falls, moderate-severe pain, use of antipsychotic medication, and physical restraints. Multivariable logistic regression models were used to assess the impact of resident's primary language, facility language, and resident-facility language discordance on each quality indicator. Results Overall, there were few differences between francophones and anglophones for quality and safety indicators. Francophones were more likely to report pain (10.9% vs 9.9%; P = .001) and be physically restrained (7.3% vs 5.2%; P < .001), whereas a greater proportion of anglophones experienced worsening of depressive symptoms (24.0% vs 22.9%; P = .001). However, quality indicators were generally worse for francophones in Non-Designated facilities, except for pain, which was more commonly reported by francophones in French-Designated facilities. Anglophones were more likely to be physically restrained in French-Designated facilities (6.7% vs 5.1%; P < .001). Conclusions and Implications For francophones, quality indicators tended to be worse in the presence of resident-facility language discordance. However, these findings did not persist after adjusting for individual- and facility-level characteristics, suggesting that the disparities observed at the population level cannot be attributed to linguistic factors alone.

Prevalence and patterns of multimorbidity among linguistic groups of patients receiving home care in Ontario: a retrospective cohort study. - Batista, Ricardo; Reaume, Michael; Roberts, Rihannon; Seale, Emily; Rhodes, Emily; Sucha, Ewa; Pugliese, Michael; Kendall, Claire E.; Bjerre, Lise M.; Bouchard, Louise; Prud'homme, Denis; Manuel, Douglas G.; et al. (BMC Geriatr., 2023)
Background Prior studies have demonstrated the negative impact of language barriers on access, quality, and safety of healthcare, which can lead to health disparities in linguistic minorities. As the population ages, those with multiple chronic diseases will require increasing levels of home care and long-term services. This study described the levels of multimorbidity among recipients of home care in Ontario, Canada by linguistic group. Methods Population-based retrospective cohort of 510,685 adults receiving home care between April 1, 2010, to March 31, 2018, in Ontario, Canada. We estimated and compared prevalence and characteristics of multimorbidity (2 or more chronic diseases) across linguistic groups (Francophones, Anglophones, Allophones). The most common combinations and clustering of chronic diseases were examined. Logistic regression models were used to explore the main predictors of ‘severe’ multimorbidity (defined as the presence of five or more chronic diseases). Results The proportion of home care recipients with multimorbidity and severe multimorbidity was 92% and 44%, respectively. The prevalence of multimorbidity was slightly higher among Allophones (93.6%) than among Anglophones (91.8%) and Francophones (92.4%). However, Francophones had higher rates of cardiovascular and respiratory disease (64.9%) when compared to Anglophones (60.2%) and Allophones (61.5%), while Anglophones had higher rates of cancer (34.2%) when compared to Francophones (25.2%) and Allophones (24.3%). Relative to Anglophones, Allophones were more likely to have severe multimorbidity (adjusted OR = 1.04, [95% CI: 1.02–1.06]). Conclusions The prevalence of multimorbidity among Ontarians receiving home care services is high; especially for whose primary language is a language other than English or French (i.e., Allophones). Understanding differences in the prevalence and characteristics of multimorbidity across linguistic groups will help tailor healthcare services to the unique needs of patients living in minority linguistic situations.

Impact of patient–family physician language concordance on healthcare utilisation and mortality: A retrospective cohort study of home care recipients in Ontario, Canada. - Reaume, Michael; Batista, Ricardo; Sucha, Ewa; Pugliese, Michael; Roberts, Rhiannon; Rhodes, Emily; Seale, Emily; Kendall, Claire. E.; Bjerre, Lise; Bouchard, Louise; Johnson, Sharon; Sood, Manish; et al. (BMJ Public Health, 2024)
Introduction As the world’s linguistic diversity continues to increase at an unprecedented rate, a growing proportion of patients will be at risk of experiencing language barriers in primary care settings. We sought to examine whether patient–family physician language concordance in a primary care setting is associated with lower rates of hospital-based healthcare utilisation and mortality. Methods We conducted a population-based retrospective cohort study of 497 227 home care recipients living in Ontario, Canada. Patient language was obtained from home care assessments while physician language was obtained from the College of Physicians and Surgeons of Ontario. We defined primary care as language concordant when patients and their rostered family physicians shared a mutually intelligible language, and we defined all other primary care as language discordant. The primary outcomes were Emergency Department (ED) visits, hospitalisations and death within 1 year of index home care assessment. Results Compared with non-English, non-French speakers who received language-discordant primary care, those who received language-concordant primary care experienced fewer ED visits (53.1% vs 57.5%; p<0.01), fewer hospitalisations (35.0% vs 37.6%; p<0.01) and less mortality (14.4% vs 16.6%; p<0.01) during the study period. In multivariable regression analyses, non-English, non-French speakers had lower risks of ED visits (adjusted hazard ratio [aHR] 0.91, 95% CI 0.88 to 0.94), hospitalisations (aHR 0.94, 95% CI 0.90 to 0.98) and death (aHR 0.87, 95% CI 0.82 to 0.93) when they received language-concordant primary care. For francophones, the risk of experiencing an ED visit, a hospitalisation or death was not impacted by the language of their family physician. Conclusions Patient–family physician language concordance is associated with a lower risk of adverse outcomes in non-English and non-French speakers. Optimising the delivery of language-concordant care could potentially result in significant decreases in the use of acute healthcare services and mortality at the population level.

Linguistic factors and COVID-19 outcomes among long-term care residents in Ontario, Canada - Reaume, Michael; Batista, Ricardo; Imsirovic, Haris; Bjerre, Lise; Kendall, Claire E.; Bouchard, Louise; Gauthier, Alain P.; Landry, Josette-Renée; Chomienne, Marie-Hélène; Muray, Mwali; Hsu, Amy; Prud'homme, Denis; et al. (BMC Geriarics, 2025)
Abstract Background The COVID-19 pandemic disproportionately affected frail individuals, especially those living in long-term care (LTC) homes. This study examined the role of linguistic factors on COVID-19 related outcomes in LTC homes. Methods We performed a population-based, retrospective cohort study of residents living in LTC homes in Ontario, Canada who were diagnosed with COVID-19 between March 31, 2020 and March 31, 2021. Resident language, obtained from LTC assessments, was used to classify residents into one of the three linguistic groups: Anglophone (English), Francophone (French), and allophone (other language). Language of the LTC home was determined using a person-time representation of the languages spoken by residents within each LTC home. We defined LTC facilities as French homes when Francophone residents contributed more than 25% of the person-days, and allophone homes when allophone residents contributed more than 50% of the person-days. Residents whose language corresponded to the language of the LTC home in which they were living were said to have received language-concordant care, while all other residents were said to have received language-discordant care. The outcomes of this study were ED visits, hospitalizations, and mortality within 90 days. Results We included a total of 26,829 LTC residents (20,315 Anglophones, 1,032 Francophones, and 5,482 allophones) living in 572 LTC homes (502 English, 28 French, 42 allophone) who were diagnosed with COVID-19. LTC residents who lived in language-discordant homes were more likely to have ED visits (adjusted HR 1.12, 95% CI 1.01–1.25) and hospitalizations (adjusted HR 1.15, 95% CI 1.02–1.29) when compared to LTC residents who lived in language-concordant homes. Residents-facility language discordance was not associated with overall mortality (adjusted HR 1.00, 95% CI 0.91–1.10) or in hospital mortality (adjusted HR 1.04, 95% CI 0.88–1.23). Conclusion Residents living in language-discordant LTC facilities experienced more ED visits and hospitalizations following diagnosis of COVID-19. The findings of this study highlight the importance of providing frail, vulnerable individuals with linguistically concordant care.